Bridge — Remedy for the Visual Impairers - Chengxi Li (Innovation in Science and Technology, 2024)
The increasing prevalence of visual impairment globally is a pressing public health issue that requires immediate action. Research has shown that there is already a tremendous amount of visual impaired around the world. As many as 1.1 billion people were thought to have vision impairment in 2020. This figure is the sum of 510 million people who had near vision loss, 258 million people with mild vision loss, 295 people with moderate to severe vision loss and 43 million people living with blindness. (Fleck, Anna, 2024) In addition to the current disturbing situation, the future trend isn’t any better. Vision loss is predicted to increase by as much as 55 percent in the next 30 years, impacting some 600 million new people, according to the ‘Vision Atlas’ report by the International Agency for the Prevention of Blindness (IAPB). By 2050, the overall figure is predicted to have risen to some 1.8 billion people, with a breakdown of 866 million people living with near vision loss, 360 million people with mild vision loss, 474 people with moderate to severe vision loss and 61 million cases of blindness (Fleck, Anna, 2024). The aging population is a primary driver; as people live longer, conditions such as cataracts, age-related macular degeneration, and glaucoma become more prevalent. The International Agency for the Prevention of Blindness (IAPB) emphasizes that “the number of persons aged 80 years or over is projected to triple from 140 million in 2019 to 420 million by 2050,” (The International Agency for the Prevention of Blindness, 2022) highlighting a demographic shift that will exacerbate the burden of vision loss. Facing the urgent situation, insurances for visual impairers’ welfare would be essential for social well-being and sustainability.